2006
DOI: 10.1128/aem.00922-06
|View full text |Cite
|
Sign up to set email alerts
|

Increased Abundance of IncP-1β Plasmids and Mercury Resistance Genes in Mercury-Polluted River Sediments: First Discovery of IncP-1β Plasmids with a Complex mer Transposon as the Sole Accessory Element

Abstract: Although it is generally assumed that mobile genetic elements facilitate the adaptation of microbial communities to environmental stresses, environmental data supporting this assumption are rare. In this study, river sediment samples taken from two mercury-polluted (A and B) and two nonpolluted or less-polluted (C and D) areas of the river Nura (Kazakhstan) were analyzed by PCR for the presence and abundance of mercury resistance genes and of broad-host-range plasmids. PCR-based detection revealed that mercury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
100
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 36 publications
2
100
1
1
Order By: Relevance
“…These plasmids and transposons include multiresistance and heavy metal resistance plasmids as, for example reported for qacA and qacB genes, respectively (Russell 1997), but they were also associated with degradative pathways in a pesticide polluted environment (Dealtry et al 2014). Class 1 integrons including qac genes are frequently found on IncP-1 plasmids which are broad host range plasmids widely distributed in the environment such as soil, manure, sludge, digestates and river sediments (Jechalke et al 2015;Smalla et al 2006;Zhang et al 2011b;Heuer et al 2012;Popowska and Krawczyk-Balska 2013;Wolters et al 2015). For example, IncP-1e plasmids were detected by qPCR in 16 manure samples and in arable soil (Heuer et al 2012).…”
Section: Role Of Qaacs In the Selection Of Antibiotic Resistancementioning
confidence: 99%
“…These plasmids and transposons include multiresistance and heavy metal resistance plasmids as, for example reported for qacA and qacB genes, respectively (Russell 1997), but they were also associated with degradative pathways in a pesticide polluted environment (Dealtry et al 2014). Class 1 integrons including qac genes are frequently found on IncP-1 plasmids which are broad host range plasmids widely distributed in the environment such as soil, manure, sludge, digestates and river sediments (Jechalke et al 2015;Smalla et al 2006;Zhang et al 2011b;Heuer et al 2012;Popowska and Krawczyk-Balska 2013;Wolters et al 2015). For example, IncP-1e plasmids were detected by qPCR in 16 manure samples and in arable soil (Heuer et al 2012).…”
Section: Role Of Qaacs In the Selection Of Antibiotic Resistancementioning
confidence: 99%
“…Plasmids of the incompatibility group P-1 (IncP-1 plasmids) transfer very efficiently to a wide range of hosts and are abundant in several environments (Thomas and Smith, 1987;Top et al, 2000;Smalla et al, 2006, Schlü ter et al, 2007. They are known to transfer at much higher rates on solid substrates than in mixed liquids.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have detected MGEs including plasmids, transposons and integrons across a wide variety of habitats (for example, Sobecky, 1999;Smalla and Sobecky, 2002;van Elsas and Bailey, 2002;Frost et al, 2005), but rarely in a quantitative manner due to previous methodological constraints. In those studies that did quantify MGE abundance in bacterial communities, class 1 integrase (intI1) genes were shown to be abundant in Gram-positive and Gram-negative bacteria in poultry litter obtained from farms with varying antibiotic usage regimes regardless of antibiotic usage (Nandi et al, 2004), while mercury exposure was recently demonstrated to increase the abundance of IncP-1 plasmids (Smalla et al, 2006). Yet, how MGE abundance is affected by environmental conditions and selective pressures is poorly understood and remains to be tested systematically.…”
Section: Introductionmentioning
confidence: 99%